2002
DOI: 10.1017/s0031182001001081
|View full text |Cite
|
Sign up to set email alerts
|

Field evidence for density-dependent facilitation amongst Ixodes ricinus ticks feeding on sheep

Abstract: Engorged Ixodes ricinus nymphs collected from sheep resident in an upland UK field site were significantly lighter than nymphs that engorged on previously tick-naïve sheep, indicating that site-resident sheep continually exposed to ticks acquired anti-tick resistance. The weights of engorged nymphs that fed on naturally tick-resistant sheep increased significantly, however, when increasingly high numbers of adult female ticks fed on the sheep during seasonal peaks of tick activity. This relationship was unaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 0 publications
1
43
1
1
Order By: Relevance
“…Bovine anaplasmosis, caused by A. marginale, is an important rickettsial disease, transmitted to cattle biologically by ticks and mechanically by biting flies and blood contaminated fomites causing significant economic losses in tropical and subtropical areas of world (Ruybal et al 2009). However, the prevalence depends largely on the distribution and density of the reservoir hosts and tick vectors (Ogden et al 2002). In the present study, examination of Giemsa stained peripheral thin blood smears revealed 1.2 % animals positive for the inclusion bodies of A. marginale.…”
Section: Discussionsupporting
confidence: 38%
“…Bovine anaplasmosis, caused by A. marginale, is an important rickettsial disease, transmitted to cattle biologically by ticks and mechanically by biting flies and blood contaminated fomites causing significant economic losses in tropical and subtropical areas of world (Ruybal et al 2009). However, the prevalence depends largely on the distribution and density of the reservoir hosts and tick vectors (Ogden et al 2002). In the present study, examination of Giemsa stained peripheral thin blood smears revealed 1.2 % animals positive for the inclusion bodies of A. marginale.…”
Section: Discussionsupporting
confidence: 38%
“…In the present study, highest incidence of B. bigemina infection was recorded in both cattle and buffaloes. The prevalence depends largely on the distribution and density of the reservoir hosts season and vectors (Singh et al, 2000;Ogden et al, 2002).The higher prevalence of bovine babesiosis can be closely correlated to the seasonal abundance of the vector Rhipicephalus microplus (Singh et al, 2000). The lower prevalence of theileriosis in bovines may be due to the lower occurrence of vector Hyalomma anatolicum anatolicum in this geographical part of the country.…”
Section: Resultsmentioning
confidence: 99%
“…However, the geographic distribution largely depends on the distribution and density of the tick vectors (Ogden et al, 2002). The rate of infection has been reported to be variable between countries and it may vary considerably even between neighbouring farms (Stuen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Migrating birds could also potentially play a role in dispersing Ehrlichia by carrying infected ticks from one country to another (Bjoersdorff et al, 2001). However, geographic distribution is largely dependent on the distribution and density of the tick vectors (Ogden et al, 2002).…”
mentioning
confidence: 99%